2022
DOI: 10.1093/jaoacint/qsac073
|View full text |Cite
|
Sign up to set email alerts
|

Different Approaches in Manipulating Ratio Spectra for Analyzing Amlodipine Besylate and Irbesartan Combination

Abstract: Background Hypertension is a key risk factor for ischemic heart disease and atherosclerosis. Most patients require a combination of antihypertensive medications to accomplish their therapeutic goals. Antihypertensive medicines such as calcium channel blockers and angiotensin receptor blockers are indicated for patients whose high blood pressure cannot be controlled with monotherapy. The combination of amlodipine besylate (AML) with irbesartan (IRB) is an example of this synergistic activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The reduction process was monitored by UV–vis spectrophotometry by scanning at definite intervals. 51 It was found that the peak of 4-NA gradually decreased at 380 nm with time and completely vanished after 270 s as shown in Figure 5 . Furthermore, a new peak corresponding to p -phenylenediamine ( p -PDA) was simultaneously observed at 240 nm.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The reduction process was monitored by UV–vis spectrophotometry by scanning at definite intervals. 51 It was found that the peak of 4-NA gradually decreased at 380 nm with time and completely vanished after 270 s as shown in Figure 5 . Furthermore, a new peak corresponding to p -phenylenediamine ( p -PDA) was simultaneously observed at 240 nm.…”
Section: Resultsmentioning
confidence: 86%
“…The catalytic activity of PBA was investigated by reducing 4-NA to utilize NaBH 4 as a reducing agent in aqueous media as presented in Figure . The reduction process was monitored by UV–vis spectrophotometry by scanning at definite intervals . It was found that the peak of 4-NA gradually decreased at 380 nm with time and completely vanished after 270 s as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…To test the generalizability of the NL values found, a total of 23 different phenolic compounds was investigated and the data are tabulated in Table 1 (all the 2D MS/MS subtracted spectrum can be found in the Figure S4). The table includes phenols significance in industrial production, environmental research, as inhibitors, therapeutic drugs, as brain metabolites, and as starting materials in synthesis of industrial, agricultural, or pharmaceutical compounds [30–38] . The phenolic compounds covered in this study showed moderate to high reactivity with PTAD.…”
Section: Resultsmentioning
confidence: 99%
“…An electroanalytical method based on a chitosan-Prussian blue nanocomposite membrane potentiometric sensor was developed to determine amlodipine selectively 12 . Additional spectrophotometric methods for assessing AM in combination with other drugs have been published and proposed [13][14][15][16] .…”
Section: Figure 1 Structure Of Amlodipine Abstractmentioning
confidence: 99%